Detecção eletroquímica de emissões ambientais em águas residuárias: análise bibliográfica - Mion, Ester Alves (Universidade Federal de São Carlos, 2025)
Environmental contamination by antibiotics is a growing concern, with negative impacts on ecosystems and public health, particularly due to the spread of antimicrobial resistance. These compounds, classified as emerging pollutants, are frequently detected in water bodies and soils, resulting from the excretion of unmetabolized residues, the release of hospital and agro-industrial effluents, and the improper disposal of pharmaceuticals. Given the need for monitoring these contaminants, electrochemical sensors have emerged as an efficient analytical alternative, offering sensitivity, selectivity, and speed in the detection of different compounds. In this review, different electrochemical sensors applied to the detection of amoxicillin, levofloxacin, cephalosporins and tetracyclines were evaluated, comparing performance, cost and applicability in different environmental matrices. The results demonstrate that sensors based on nanomaterials, molecularly imprinted polymers, and metal oxides exhibit high efficiency in identifying these compounds, making them a viable and sustainable option for environmental monitoring. Advancements in the development of electrochemical sensors represent a significant step toward more efficient antibiotic monitoring, reducing costs and environmental impacts. Furthermore, the implementation of stringent public policies regarding the use and disposal of antibiotics is essential to minimize pollution and curb the spread of antimicrobial resistance. The combination of different analytical approaches and the continuous development of new detection technologies are crucial to addressing the challenges posed by antibiotics as emerging pollutants.
Electrochemical detection of environmental emissions in wastewater: bibliographic analysis
Keywords: Antibióticos; Poluentes emergentes; Sensores eletroquímicos; CIENCIAS EXATAS E DA TERRA::QUIMICA